Effect of organosilicon adsorbent on the content of mobile forms of heavy metals and growth of test-crop under conditions of soil contamination with lead and copper - P. D. Skurikhina (Бюллетень Почвенного института им. В.В. Докучаева, 2023)
The pollution of soil by heavy metals becomes a prime ecological problem. Recultivation of polluted soil objects is usually made by means of different types of sorbents. So, in this connection the search for the most effective and multifunctional sorbing agent is relevant. The model experiment of soil pollution by several heavy metals in upper soil horizon was carried out. The soil for that research was Grey-Luvic Phaeozems. Lead (Pb2+) and copper (Cu2+) were chosen as pollutants. Solutions of lead acetate (Pb(CH₃COO)₂·3H2O) and copper sulphate (CuSO₄·7Н2O) of three different concentrations (1 MPC, 5 MPC, 10 MPC) were used as pollutants. Solutions of organosilicon adsorbent – 1,1,3,3,3-tetrahydroxy-1,3-dimethyldisiloxane polyhydrate (PMSPG) were also applied in three different variants: 0.01%; 0.1%; 1%. The mobile forms of heavy metals were researched by method of atomic absorption spectrometry. The mobile forms of heavy metals were extracted by the ammonium acetate buffer (pH = 4.8). According to results, the application of organosilicon sorbent had a positive issue. Application of adsorbent significantly reduced the concentrations of mobile heavy metal compounds. The application of PMSPG solution with concentration of 1% was the most effective. A vegetation experiment was carried out. Cress (Lepidium sativum L.) of “Zabava” variety was used as a test-crop. Favourable changes in the growth of cress with the use of adsorbent at the concentration of 1% compared to the control variants were revealed.